Evaluating the role of atazanavir/cobicistat and darunavir/cobicistat fixed-dose combinations for the treatment of HIV-1 infection - Crutchley RD (Dove Medical Press, 2016)
Rustin D Crutchley,1 Rakesh C Guduru,2 Amy M Cheng1 1Department of Pharmacy Practice and Translational Research, College of Pharmacy, University of Houston, 2CompanionDX, Houston, TX, USA Abstract: Atazanavir/cobicistat (ATV/c) and darunavir/cobicistat (DRV/c) are newly approved once daily fixed-dose protease inhibitor combinations for the treatment of HIV-1 infection. Studies in healthy volunteers have established bioequivalence between cobicistat and ritonavir as pharmacoenhancers of both atazanavir (ATV) and darunavir (DRV). In addition, two randomized clinical trials (one Phase II and one Phase III noninferiority trial with a 144-week follow-up period) demonstrated that cobicistat had sustainable and comparable efficacy and safety to ritonavir as a pharmacoenhancer of ATV through 144 weeks of treatment in HIV-1-infected patients. Furthermore, one Phase III, open-label, single-arm, clinical trial reflected virologic and immunologic responses and safety outcomes consistent with prior published data for DRV/ritonavir 800/100 mg once daily, supporting the use of DRV/c 800/150 mg once daily for future treatment of treatment-naïve and -experienced HIV-1-infected patients with no DRV resistance-associated mutations. Low rates of virologic failure secondary to resistance to antiretroviral regimens were present in these clinical studies. Most notable adverse events in the ATV studies were hyperbilirubinemia and in the DRV study rash. Small increases in serum creatinine and minimally reduced estimated glomerular filtration rate Cockcroft–Gault calculation (eGFRCG) were observed in ATV/c and DRV/c clinical studies consistent with other studies evaluating elvitegravir/cobicistat/tenofovir/emtricitabine for the treatment of HIV-1 infection. These renal parameter changes occurred acutely in the first few weeks and plateaued off for the remaining study periods and are not necessarily clinically relevant. Cobicistat has numerous advantages compared to ritonavir such as fewer drug–drug interactions, being devoid of anti-HIV-1 activity, as well as it has better solubility affording coformulation with other antiretrovirals as simplified fixed-dose combinations. Overall, the recent approval of ATV/c and DRV/c offers HIV patients opportunities for improved adherence to lifelong treatment. Future studies are warranted to determine the efficacy and safety of ATV/c and DRV/c in treatment-experienced patients. Keywords: atazanavir, darunavir, cobicistat, HIV protease inhibitors, treatment simplification